Development of Interactive Learning Video Media to Improve Mathematical Representation Ability on Data Presentation Material - A. Sriyanti; Syarifah Ainur Natia; Mutahharah Yunus; Nurwahyuni; Dini Aprilia; Masniati (Mathematics Education Journal, 2024)
One of the main challenges in learning mathematics is overcoming students' difficulties in understanding abstract mathematical material and the lack of engaging and interactive teaching methods. The aim of this research is to develop interactive learning videos that are valid, effective, and practical. This Research and Development (R&D) study uses the ADDIE model. The research subjects were 15 students of class VII A MTsS Ash-Shalihin.. The results of the study show that the interactive learning video is highly valid with a score of 3.7 from expert evaluations. Teacher responses received a score of 3.67, which is categorized as very practical, while student responses received a score of 3.34, indicating that the video is very effective. The t-test and N-Gain test showed a value of 0.67, indicating an improvement in students' mathematical representation abilities in the moderate category. Thus, the learning video has proven to be effective.